Dampak Perubahan Terhadap Jam Kerja dan Stres Kerja Terhadap Kinerja Karyawan - Wahyuni, Indri; Kurnianto, Munding; Hermawan, Ian; Saputra, M Ridwan; Nurrahman, Dian (Universitas Pahlawan Tuanku Tambusai, 2025)
Changes in working hours and levels of work stress are two important factors that can affect employee performance in organizations. This study aims to examine how changes in working hours, both in terms of duration and pregnancy, and high work pressure impact employee work effectiveness. Using a literature study approach, this article analyzes various literature from previous studies to find patterns of relationships between these variables. The results of the study indicate that unplanned changes in working hours can increase stress and decrease productivity, while flexible working hour arrangements tend to improve work-life balance and performance. Therefore, organizations need to consider work time management and stress management as part of a strategy to improve employee performance.